2009
DOI: 10.2174/1874262900903010001
|View full text |Cite
|
Sign up to set email alerts
|

Natural Fragmentation Model of Zirab Coals, Iran

Abstract: Iran's coals occur in the Alborz range (north) and Central Iran basins. The Zirab is typical coalfield in the Alborz coal basin. From litho types of view, the coals are mainly clarovitrinite to clarodurite type which are used as source of coking coal for metallurgical factories. During the research we used 10 typical samples from Zirab coal mine to estimate fragmentation model of natural particle-size distribution of these coals. Prediction of natural fragmentation properties from coals was the main aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Hartmann (1969) suggested that the discrepancy between lognormal and power-law fi ts is in part due to limitations of observational methods , which must always undercount the smallest particles. Some studies have shown that fragmentation processes can produce fragments that are best described as either mixed lognormal-power law or two-power-law populations (e.g., Meibom and Balslev, 1996;Tavassoli and Shirvani, 2000;Yazdi and Esmaeilnia, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Hartmann (1969) suggested that the discrepancy between lognormal and power-law fi ts is in part due to limitations of observational methods , which must always undercount the smallest particles. Some studies have shown that fragmentation processes can produce fragments that are best described as either mixed lognormal-power law or two-power-law populations (e.g., Meibom and Balslev, 1996;Tavassoli and Shirvani, 2000;Yazdi and Esmaeilnia, 2009). …”
Section: Introductionmentioning
confidence: 99%